Christian counseling ethics : a handbook for psychologists, therapists and pastors - Sanders, Randolph K.; Christian Association for Psychological Studies (Downers Grove, Illinois : IVP Academic, 2013)
The work of psychotherapy and counseling is full of ethical challenges and dilemmas. Responding to these situations with wisdom is critical, not only for the professional's credibility, but also for good therapeutic relationships and positive treatment outcomes. Since its first publication, Christian Counseling Ethics has become a standard reference work for Christian psychologists, counselors and pastors and a key text at Christian universities and seminaries. This thoroughly revised edition retains core material on counseling ethics that has made it so valuable in a variety of settings. Now fully updated, it weighs and assesses new and emerging ethical issues in the field.
Embracing our ethical mandate / Randolph K. Sanders -- Psychotherapy and Christian ethics / Alan C. Tjeltveit -- Qualifications of the Christian mental health professional / Richard E. Butman -- Essential elements for ethical counsel / Horace C. Lukens, Jr. & Randolph K. Sanders -- Sexual misconduct and the abuse of power / John F. Shackelford & Randolph K. Sanders -- Nonsexual multiple relationships / Randolph K. Sanders -- Ethics in couples therapy / Jennifer S. Ripley, Steven J. Sandage & Everett L. Worthington, Jr. -- The child client / Jeffrey S. Berryhill & Angela M. Sabates -- Addressing spiritual and value issues in therapy / Randolph K. Sanders -- The sexual minority client / Mark A. Yarhouse, Jill L. Kays & Stanton L. Jones -- Clients with chronic conditions / James H. Jennison -- Ethical concerns in culturally sensitive practice / Sally Schwer Canning, Iryna Shturba Arute, Andrea M. Librado & Anta Yu -- Business ethics in mental health service / Randolph K. Sanders -- Pastors who counsel / Bill Blackburn -- Lay counselor training / Siang-Yang Tan -- Mixed agency dilemmas for professionals in the military and other government agencies / W. Brad Johnson -- Ethical issues in university counseling centers / Roderick D. Hetzel, Cassie Kendrick & Susan Matlock-Hetzel -- Ethics in member care : toward an international framework / Kelly O'Donnell -- Ethics providing psychological first aid / Cynthia B. Eriksson & Thomas C. Duke -- Training programs / Tamara L. Anderson, Gregory R. Schneller & John Eric Swenson III -- A model for ethical decision-making / Randolph K. Sanders -- Ethical codes & guidelines.
Includes bibliographical references and index.
Keywords: Pastoral counseling -- Moral and ethical aspects; Counselors -- Professional ethics